2014
DOI: 10.4103/1673-5374.135329
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: a double-edged sword for neuronal survival after cerebral ischemia

Abstract: Evidence suggests that autophagy may be a new therapeutic target for stroke, but whether activation of autophagy increases or decreases the rate of neuronal death is still under debate. This review summarizes the potential role and possible signaling pathway of autophagy in neuronal survival after cerebral ischemia and proposes that autophagy has dual effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(43 citation statements)
references
References 72 publications
2
41
0
Order By: Relevance
“…However, emerging evidence indicated that the self‐cannibalistic function may be associated with excessive cell death under certain conditions31, 32 Therefore, more and more scholars described the role of autophagy in various pathophysiological processes as a double‐edged sword 33, 34, 35, 36. From the previous study, the autophagy was proved to be a protective role for AKI37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence indicated that the self‐cannibalistic function may be associated with excessive cell death under certain conditions31, 32 Therefore, more and more scholars described the role of autophagy in various pathophysiological processes as a double‐edged sword 33, 34, 35, 36. From the previous study, the autophagy was proved to be a protective role for AKI37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Stroke results in multiple complications that can affect the economic welfare and daily function of individuals [10,11]. Cerebral ischemic disease is one of the five leading causes of death that also includes cardiac disease, cancer, chronic lower respiratory disease, and trauma [12].…”
Section: Erythropoietin and Traumatic Brain Injury: Translating Expermentioning
confidence: 99%
“…In regards to autophagy during DM, this pathway of programmed cell death may have variable outcomes (141). Autophagy recycles cytoplasmic components and discards defective organelles for tissue remodeling (125, 142).…”
Section: Dm Apoptosis and Autophagymentioning
confidence: 99%
“…However, it should be noted that autophagy might not be consistently beneficial (128, 141, 146). Under some conditions, autophagy may be less of a prominent modulator of cell survival than apoptosis in some experimental models (147).…”
Section: Dm Apoptosis and Autophagymentioning
confidence: 99%